Intepreters of Luther - Mortensen, Viggo (Grundtvig-studier, 1971)
Interpreters of Luther. Essays in Honor of Wilhelm Pauck Reviewed by Viggo Mortensen The reason why this book is mentioned here is that it includes articles on Grundtvig’s and Kierkegaard’s views on Luther. A paper on Grundtvig and Luther is written by Ernest D. Nielsen, President of Grand View College, Iowa, who gives an introduction to Grundtvig’s thoughts on human life and Christianity by comparing them with Luther’s relatively well known opinions. The account is based on Den christelige Børnelærdom and Den danske Statskirke upartisk betragtet ( 1834), an^ inspiration from Kaj Thaning’s interpretation of Grundtvig is obvious, but the article does not claim to be more than an introduction to Grundtvig. A deeper analysis of the difference between Grundtvig’s and Luther’s views on man would be extremely important, however. The fact that there is a difference has been shown by Thaning (Menneske først, p. 661 ff.), and through genetico-historical investigations Michelsen has shown what this difference consists in as far as the conception of history is concerned (Tilblivelsen af Grundtvigs historiesyn, p. 127 ff.).In Denmark there is an increasing dislike against mentioning both Kierkegaard and Luther as one’s spiritual ancestors; K. E. Løgstrup is more inclined to mention Grundtvig and Luther because of the importance both of them attach to the Creation.— But are Kierkegaard’s and Luther’s views on Christianity compatible? This has never been documented in detail. Up till now scholars have contended themselves with elucidating what Kierkegaard thought about Luther, and it has been demonstrated that, gradually, Kierkegaard became more and more critical against Luther. The exception to this general tendency is Johs. Sløk’s article in Kierkegaardiana II, 1957. Only rarely has the question been analysed in a systematic way. Ernest B. Koenker’s article in the volume under review is no exception. The author is a professor of history at the University of South California. He demonstrates that the decisive points of controversy are their opinion about the Passion and the paradox of faith. According to Kierkegaard the Passion originates in the clash between the temporal and the eternal, i. e. the absolute that is the central concept in Kierkegaard’s conception of Christianity. Koenker’s essay does not claim to be a work of original research, but is does give a precise formulation of the questions to be dealt with in future research.